Influence of Sulfonated-Kaolin On Cationic Exchange Capacity Swelling Degree and Morphology of Chitosan/Kaolin Composites - Ozi Adi Saputra; Dheo Adha Saputra; Kartika Setia Rini; Edi Pramono (Chemistry Department, The University of Brawijaya, 2016)
Preparation of sulfonated-kaolin (sKao) has been conducted and used as filler on chitosan matrix via solution casting method, namely chitosan/sKao (Cs/sKao). Swelling degree, cationic exchange capacity and thermal stability were evaluated to determine chitosan/sKao membranes performance as proton exchange membrane in fuel cell. Functional group analysis of chitosan, sKao and synthesized products were studied using Fourier Transform Infra-Red (FTIR) spectroscopy. In this study, swelling degree and swelling area of Cs/sKao are also studied to determine of membrane ability to swelling which compare to unmodified chitosan/kaolin (Cs/Kao). The presence of sKao in chitosan matrix was able to improve cationic exchange capacity (CEC) which proved by morphological study of membrane surface after CEC test. Moreover, Thermal stability of Cs/sKao showed the membrane has meet requirement for PEM application.